Faktor-faktor yang berhubungan dengan kecemasan ibu hamil primigravida trimester III di wilayah kerja Puskesmas Sungai Pinang Kecamatan Sungai Pinang Kabupaten Ogan Ilir - Elsi Parina; rohaya rohaya; Eka Afrika (NHM PRESS, 2023)
Anxiety is an old feeling of fear of something that is not clear and associated with feelings of uncertainty and helplessness. The World Health Organization (WHO) stated that anxiety for pregnant women in developed countries has an prevalence of around 7-20% and in developing countries it is more than 20%. The purpose of this study was to determine the factors associated with the anxiety of third-trimester primigravida pregnant women in the Working Area of the Sungai Pinang Community Health Center, Sungai Pinang District, Ogan Ilir Regency in 2023. The research design used an analytical survey with a cross sectional approach. The population in this study were pregnant women who came to check their pregnancy at the Sungai Pinang Health Center, Sungai Pinang District, Ogan Ilir Regency in June-July 2023, totaling 31 people. The sampling technique in this study was carried out by purposive sampling with a total sample of 31 respondents. Collecting data using a questionnaire sheet. Data analysis used univariate analysis and bivariate analysis using the chi square test. The results of the study showed that there was a relationship between age (p value = 0.027), education (p value = 0.038), frequency of ANC (p value = 0.003) and husband's support (p value = 0.043) with the anxiety of third trimester primigravida pregnant women at the Sungai Pinang Community Health Center, Sungai Pinang District. Pinang Ogan Ilir Regency in 2023. It is hoped that the results of this research can become policy material or consideration for the puskesmas to be able to provide solutions such as by holding regular classes for pregnant women, providing health education and counseling to pregnant women on a regular basis to reduce psychological problems for pregnant women especially anxiety in the third trimester.